1982
DOI: 10.1080/15287398209530302
|View full text |Cite
|
Sign up to set email alerts
|

Paternal effects of ethanol in the long‐Evans rat

Abstract: Ten male Long-Evans rats were given 20% v/v ethanol in the drinking water for 60 consecutive days. Ten other males were given distilled water and served as controls. Each male was then allowed to mate with three virgin female Long-Evans rats, once per week for three consecutive weeks. The males were necropsied after the third mating, the females were killed on d 20 of gestation, and the offspring were examined for parameters of fetal growth, skeletal ossification, and soft-tissue anomalies. Ethanol caused test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…This study confirms the association between paternal alcohol exposure and decreased fetal weight (Mankes et al, 1982;Tanaka et al, 1982) and an increased frequency of runting (Bielawski and Abel, 1997). Males and females were randomly assigned, and there were initially no differences in body weight across groups.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This study confirms the association between paternal alcohol exposure and decreased fetal weight (Mankes et al, 1982;Tanaka et al, 1982) and an increased frequency of runting (Bielawski and Abel, 1997). Males and females were randomly assigned, and there were initially no differences in body weight across groups.…”
Section: Discussionsupporting
confidence: 78%
“…I N CONTRAST TO the large body of research characterizing the deleterious effects of maternal alcohol consumption on fetal development and the mechanisms of these effects [for review, see Abel (1998)], the role of paternal alcohol consumption on offspring development has received little attention. However, paternal alcohol exposure is also associated with increased malformations, growth retardation, and behavioral anomalies in offspring, as well as an unusual susceptibility to infection (e.g., Abel, 1991Abel, , 1993aBerk et al, 1989;Bielawski and Abel, 1997;Bielawski et al, 1995;Hazlett et al, 1989;Mankes et al, 1982;Tanaka et al, 1982). One reason paternally mediated effects have not been as actively investigated is that the mechanisms underlying these effects have yet to be elucidated (Abel, 1998).…”
mentioning
confidence: 99%
“…First, contrary to our findings in Finegersh & Homanics 2014 that paternal CIE increases postweaning body weight in hybrid male offspring, here, there was a small, but significant reduction of postweaning body weight in E-sired male offspring on an inbred background. However, this outcome is not surprising given that many paternal ethanol exposure studies have found either increased or decreased offspring body weight using different rodent strains or exposure paradigms (Knezovich & Ramsay, 2012; Ledig et al, 1998; Mankes et al, 1982). The second inconsistency between studies is the absence of an effect of paternal CIE on acute HPA axis responsivity in F1 inbred male offspring, counter to our published findings showing that paternal CIE produced stress hyporesponsivity phenotypes in F1 hybrid male offspring (Rompala et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…However, and some exceptions aside, a definite trend is evident with increasing exposure that reflects reduced birth weight in the offspring [62-64], fewer offspring [64,65], and an increased number of malformations [64,66], including dysmorphic craniofacial features and behavioral or cognitive effects [67-70]. …”
Section: Epigenetic Remodeling and Vulnerability To The Teratogenic Ementioning
confidence: 99%